Child migration in Africa - Hashim, Iman.; Thorsen, Dorte; Nordiska afrikainstitutet (London ; New York : Zed Books ; Uppsala, Sweden : In ass ociation with the Nordic Africa Institute, 2011)
Child Migration in Africa explores the mobility of children without their parents within West Africa. Drawing on the experiences of childre n from rural Burkina Faso and Ghana, the book provides rich material on the circumstances of children's voluntary migration and their experien ces of it. Part of the groundbreaking Africa Now series, Child Migratio n in Africa is an important and timely contribution to an under-researc hed area.
Includes bibliographical references (p. 132-144) and index.
Keywords: Unaccompanied immigrant children -- Africa, West; Children -- Africa, West -- Social conditions